PEDAGOGIC COMPETENCE OF AGRO-INDUSTRY TECHNOLOGY EDUCATION STUDENTS WHO PARTICIPATE IN PPLSP AND KAMPUS MENGAJAR - Febia Andriani; Sri Handayani; Dwi Lestari Rahayu (PEDAGOGIA, 2022)
Students of the Agroindustrial Technology Education Study Program who take part in the Kampus Mengajar program are feared to have lower pedagogic competence than students who take the Education Unit Field Introduction Program (PPLSP). This study aimed to determine the level of pedagogic competence of students of the Agroindustrial Technology Education Study Program who took part in the 2021 PPLSP and the Kampus Mengajar Program Batch 2 and the differences in pedagogic competence in the two groups of students. Pedagogic competence is measured based on students' perceptions by filling out a closed questionnaire. There are 10 pedagogic competence indicators described in 30 statements in the questionnaire. The questionnaire was filled out by 40 students who took part in the 2021 PPLSP and 17 students who took part in the Kampus Mengajar  Program 2. Structured interviews to obtain additional data were then conducted with 28 people who were randomly selected from the group of students who took part in the PPLSP and the Teaching Campus. The results showed that the pedagogic competence of students who took part in the 2021 PPLSP and the Kampus Mengajar Batch 2 were in the high category. However, three statements of pedagogical competence are considered to be in the medium category for PPLSP 2021 students but high for Class 2 Kampus Mengajar students on Kampus Mengajar students Batch 2.